'I can't draw, sing or dance to save my life!': Educator and parent implicit theories of creativity. Issue 2 (June 2023) - Fielding, Katie; Maslin, Kimberly; Murcia, Karen
Creativity is recognised as a key facet of the suite of 21st century skills driving education worldwide. Understanding its existence outside of The Arts is vital for recognising young children's creativity. However, what constitutes creativity and what it 'looks like' is not always clear. As a result, inconsistency and lack of efficacy when educators and parents attempt to encourage the development of young children's creativity is possible. To investigate implicit theories of creativity relating to what creativity is and who is considered creative, parents and educators of four to eight-year-old children in four early learning contexts in Perth, Western Australia, were invited to complete a questionnaire. Findings suggest there may not be a strong tendency towards recognising creativity in The Arts but there may be an inclination to recognise eminent men's creativity more than women's. Additionally, there appears to be a lack of recognition of 'daring' as a creative behaviour.